The incidence, calf morbidity and mortality due to Theileria parva infections in smallholder dairy farms in Murang'a District, Kenya - Gitau, G.K.; Perry, Brian D.; McDermott, John J. (Elsevier, 1999)
A prospective observational study was conducted among smallholder dairy farmers in Murang'a District, Kenya, to estimate the incidence of Theileria parva infections, as well as calf morbidity and mortality caused by the infection. The study was conducted between March 1995 and August 1996, in five cohorts of female calves from birth to six months of age from different agro-ecological zones (AEZs) and grazing-system strata shown previously to have varying prevalences of T. parva infection. A total of 188 smallholder dairy farms with 225 female calves were selected purposively by five AEZ-grazing strata. All recruited calves were visited within the first two weeks of life and thereafter at biweekly intervals up to the age of six months. The mean number of cattle in these smallholder farms was 2.6. Both exotic and indigenous breeds of cattle and their crosses were present, with the former predominating. The incidence (27-54 percent) of sero-conversion to T. parva in an ELISA test was significantly different (p<0.05) accross the five AEZ-grazing strata and increased with lower elevation and unrestricted grazing. Calf morbidity and mortality were also variable across the AEZ-grazing strata. East Coast fever (ECF) was the highest-incidence cause calf morbidity and mortality (relative to other diseases). There are great differences in the epidemiology of ECF within a small area and this implies that there is need to carefully consider different ECF control strategies in different AEZ-grazing strata.